Hydroponics for Food Self-Sufficiency in an Urban Pesantren: Evidence of Reduced Vegetable Expenditure and Improved Student Competencies - Dwi Budi Santoso; Dynda Fadhlillah Aulia (LP2M INSURI Ponorogo, 2026)
Islamic boarding schools (pesantren) in Indonesia are increasingly developing as centers of community empowerment. However, daily food provision remains a challenge, especially in urban areas with limited land and budget constraints. This community service program used a Participatory Action Research (PAR) approach to develop a hydroponics-based urban farming model to strengthen food self-sufficiency and improve students’ practical agribusiness skills. Conducted over one year, the program involved needs assessment, socialization, hydroponics training, greenhouse installation, and ongoing mentoring. A total of 22 participants completed the program. The hydroponic unit achieved four harvest cycles, producing an estimated 96–104 kg of leafy vegetables annually. With a local retail value of around Rp18,000 per kg, the harvest contributed an estimated annual food savings of Rp1.7–1.9 million. Competency assessment also showed notable improvement, with average participant scores increasing from 52 to 82. These findings indicate that hydroponics offers a practical, scalable, and low-space solution for supporting food resilience and skill development in urban pesantren